Karakterisasi Dan Potensi Pemnafaatan Palm Oil Mill Effluent (POME) - Dikki Awanda; David Andrio; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Palm Oil Mill Effluent (POME) contains high concentrations of organic pollutants. The high organic concentration in POME makes it suitable reused as an energy source. This study aims to investigate the characteristics of POME and analyze the potential of POME. The results of this study indicate the concentration of total and soluble COD in POME 32,000 mg / L and 16,000 mg / L, VSS amounting to 6,000 mg / L and pH 4.2. With high organic concentration then POME can be utilized as bioethanol and biogas. Keywords: Palm Oil Mill Effluent (POME)